SPINDLE MEMBRANES DURING SPERMATOGENESIS IN DERMATOBIA-HOMINIS (DIPTERA, CUTEREBRIDAE) - QUAGIOGRASSIOTTO, I; Lello, E. (Journal Submicroscopic Cytology Pathology, 1995)
During the mitotic and meiotic division in Dermatobia hominis spermatogenesis, the nuclear envelope is fragmented and membranes appear around the spindle. The membranes surrounding the mitotic spindle are formed by two layers of cisterns. The membranes of the meiotic spindle consist in at least 3 or 4 layers of long smooth cisterns which isolate the spindle from the remaining cytoplasm. The presence of this kind of membranes during meiosis seems to be usual in insect male germ cell.
Keywords: DERMATOBIA HOMINIS; SPERMATOGENESIS; MITOSIS; MEIOSIS; SPINDLE MEMBRANES